Valorization of Passiflora ligularis Shells for the Eco‐Friendly Production of Zinc- and Copper-Oxide Nanoparticles - Camacho Valencia, Daniela; Tacusi Oblitas Taco, Ariadne Maria; Ramirez Revilla, Stamber; Márquez, Gerson José (LACCEI, 2025)
Passiflora ligularis (granadilla) is widely cultivated in tropical regions across the Americas. Its consumption generates waste, such as peels, that are typically discarded. In line with the principles of the circular economy, this study explores the green synthesis of metal oxide nanoparticles using granadilla shell extract, with potential applications in antimicrobial treatments and in the remediation of water contaminated with heavy metals or textile dyes. ZnO, CuO, and mixed Zn-Cu oxide nanoparticles were synthesized via an eco-friendly coprecipitation method, using the peel extract as a natural complexing and capping agent. The nanoparticles were characterized by electron diffraction, transmission electron microscopy, energy-dispersive X-ray spectroscopy, and infrared spectroscopy to determine their crystalline structure, morphology, size, aggregation state, and elemental composition. The nanoparticles obtained were ultra-small (3-5 nm), with low crystallinity. ZnO exhibited a hexagonal wurtzite structure, while CuO showed a monoclinic phase. The mixed Zn-Cu oxide displayed a Zn:Cu atomic ratio of approximately 1:3, corresponding to the formula Zn0.25Cu0.75O. The results suggest that granadilla shells are a viable green resource for synthesizing metal oxide nanoparticles with high specific surface areas, making them promising candidates for environmental and antimicrobial applications.